Herpes simplex virus antiviral chemotherapy - Field, Hugh J. (Henry Stewart Talks, 2011)
Herpes simplex virus type-1 & type-2, Common diseases caused by HSV, HSV infections are life-long, All viruses are obligate intracellular parasites, HSV-the first virus treated effectively with antivirals, Findings for antiviral compounds, Nucleoside analogues: successful HSV inhibitors, Acyclovir & penciclovir have similar activity, low aqueous solubility, Prudrugs conversion yields active compounds, Remaining problems in HSV disease management